Corporate Management Needs Internal Audit - Li , Jun (Journal of Theory and Practice of Management Science, 2023)
Under the environment of market economy system, companies are faced with severe pressure of market competition. From the perspective of sustainable development of the company, internal audit plays a vital role. As a basic content of the company's financial management, internal audit is an important guarantee for the normal operation of the company, and also a sword for the company to expand its market share and achieve stable and sustainable development. Based on this, the development of internal audit work is the inevitable demand of company management.